Etnomatematika: Eksplorasi Motif Ulos Batak Toba Dalam Pembelajaran Bangun Datar - Aruan, Anggie Desi K. (Sepren, 2024)
This research aims to explore examples of mathematical ideas found in the motifs of Batak Toba ulos fabric used in wedding ceremonies. Despite being derived from dialogues and observations, it was found that geometric principles such as symmetry, transformation, reflection, and repetition are manifested in the creation of Batak Toba ulos fabric for wedding ceremonies. Additionally, mathematical concepts such as straight lines, curves, circles, and polygonal shapes like triangles, squares, stars, hexagons, octagons, pyramids, and parallelograms are also present in the motifs of Batak Toba ulos fabric. This knowledge is crucial to be learned and taught to students as a source in contextual learning. Furthermore, it provides new insights to students about the diverse facets of mathematical knowledge, not just as a formal subject in school. Thus, mathematics learning can commence from real-life situations experienced by students.